Introduction to the Contemporary Musical Composition “Life Style” | Pengantar Komposisi Musik Kontemporer “Life Style” - I Putu Gede Wira Satya (GHURNITA: Jurnal Seni Karawitan, 2021)
This Life Style work was created because the stylist wanted to convey the message that it is important for us to change our lifestyle so that we can feel the difference between the past and the present life. This makes us feel the phases of changing lifestyles or the differences in life from the past and living now in order to show our identity and progress for the future. Just as humans cannot be shackled in the past, therefore lifestyle changes and lifestyle differences teach us to think with one commitment and find identity and self-improvement. Alma Hawkin's creative method was used to compose this contemporary piece of music. This Life Style music piece consists of two parts: the first part which analogizes the lifestyle of the former stylists and the second part which analogizes the changes and differences in the lifestyle of the present stylist when carrying out a healthy lifestyle.